Adverse developmental impacts in progeny of zebrafish exposed to the agricultural herbicide atrazine during embryogenesis - Janiel K. Ahkin Chin Tai; Katharine A. Horzmann; Thomas L. Jenkins; Isabelle N. Akoro; Sydney Stradtman; Uma K. Aryal; Jennifer L. Freeman (Environment International, 2023)
Atrazine (ATZ) is an herbicide commonly used on crops in the Midwestern US and other select global regions. The US Environmental Protection Agency ATZ regulatory limit is 3 parts per billion (ppb; µg/L), but this limit is often exceeded. ATZ has a long half-life, is a common contaminant of drinking water sources, and is indicated as an endocrine disrupting chemical in multiple species. The zebrafish was used to test the hypothesis that an embryonic parental ATZ exposure alters protein levels leading to modifications in morphology and behavior in developing progeny. Zebrafish embryos (F1) were collected from adults (F0) exposed to 0, 0.3, 3, or 30 ppb ATZ during embryogenesis. Differential proteomics, morphology, and behavior assays were completed with offspring aged 120 or 144 h with no additional chemical treatment. Proteomic analysis identified differential expression of proteins associated with neurological development and disease; and organ and organismal morphology, development, and injury, specifically the skeletomuscular system. Head length and ratio of head length to total length was significantly increased in the F1 of 0.3 and 30 ppb ATZ groups (p < 0.05). Based on molecular pathway alterations, further craniofacial morphology assessment found decreased distance for cartilaginous structures, decreased surface area and distance between saccular otoliths, and a more posteriorly positioned notochord (p < 0.05), indicating delayed ossification and skeletal growth. The visual motor response assay showed hyperactivity in progeny of the 30 ppb treatment group for distance moved and of the 0.3 and 30 ppb treatment groups for time spent moving (p < 0.05). Due to the changes in saccular otoliths, an acoustic startle assay was completed and showed decreased response in the 0.3 and 30 ppb treatments (p < 0.05). These findings suggest that a single embryonic parental exposure alters cellular pathways in their progeny that lead to perturbations in craniofacial development and behavior.